Elucidando a prevalência de estupro no Brasil a partir de diferentes bases de dados - Helder Ferreira de Mendonça; Danilo Santa Cruz Coelho; Daniel Cerqueira; Paloma Palmieri Alves; Marcella Semente (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The aim of this Discussion Paper was to estimate the attrition rate of rape in the health and police systems. From a joint analysis of the National Health Survey from Brazilian Institute of Geography and Statistics (Pesquisa Nacional de Saúde do Instituto Brasileiro de Geografia e Estatística - PNS/IBGE) and on the Notifiable Diseases Information System (Sistema de Informaç\~ao de Agravos de Notificaç\~ao - Sinan) from the Ministry of Health, we made an approximate calculation for the number of rapes in Brazil, which would be at a level of 822 thousand per year. It corresponds to the occurrence of at least two rapes per minute in Brazil. From this number, it was possible to estimate that only 8.5% of rapes are being identified by the police and only 4.2% by the health system.
Keywords: I10; K42; 330; rape; Brazil; sexual violence; Sinan; National Health Survey